HUBUNGAN ANTARA PENGETAHUAN IBU NIFAS TENTANG INISIASI MENYUSU DINI DENGAN PENERAPANNYA - Sherly Jeniawaty; Queen Khoirun Nisa Mairo; Dewi Yudha Puspitasari (JURNAL PENELITIAN KESEHATAN, 2016)
Knowledge is the whole idea, ideas, ideas, concepts, and an understanding of the humanworld and everything in it, including man and his life. Results of preliminary studies in BPSIstiqomah Surabaya of 10 puerperal women, as many as five people (50%) lack of knowledgeabout the early initiation of breastfeeding and do not apply. The title of this research is theknowledge of puerperal women about early initiation of breastfeeding with the application.The purpose of this study was to analyze the relationship between postpartum maternalknowledge about early initiation of breastfeeding with the application. This research usesobservational analytic study and selection of samples by simple random sampling. The populationused was treated in the postpartum mother BPS Istiqomah Surabaya. Large sample studied was 53for women. The independent variables in this study is the knowledge of puerperal women aboutearly initiation of breastfeeding, while the dependent variable is the application.The results showed that out of 53 respondents largely postpartum mothers postpartum motherslack knowledge about early initiation of breastfeeding 43 (81.13%) and does not apply. The resultsof chi-squre calculation is greater than the calculation tables. Null hypothesis is rejected becausethe results χ²hitung (45.36) χ²tabel (3.84) with a significance level (0.05), meaning that there isa relationship between postpartum maternal knowledge about early initiation of breastfeeding withtheapplication.Conclusions This study shows that knowledge of puerperal women about earlyinitiation of breastfeeding less, so the application does not do.Suggestions from this study is that midwives should further improve communication,information, and motivation on postpartum about early initiation of breastfeeding so inisiai earlyfeeding may be applied.